2021
DOI: 10.1038/s41598-021-97657-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel cryo-EM structure of an ADP-bound GroEL–GroES complex

Abstract: The GroEL–GroES chaperonin complex is a bacterial protein folding system, functioning in an ATP-dependent manner. Upon ATP binding and hydrolysis, it undergoes multiple stages linked to substrate protein binding, folding and release. Structural methods helped to reveal several conformational states and provide more information about the chaperonin functional cycle. Here, using cryo-EM we resolved two nucleotide-bound structures of the bullet-shaped GroEL–GroES1 complex at 3.4 Å resolution. The main difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 68 publications
1
11
1
Order By: Relevance
“…It is very probable that altering the physiological conditions may lead to a change in the steps of the functional cycle. For example, in high ADP concentration, the release of the ADP step is skipped [ 4 ]. Functional tests have indicated that the substrate-binding surface lies on the two α-helices (H and I) of the apical domain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is very probable that altering the physiological conditions may lead to a change in the steps of the functional cycle. For example, in high ADP concentration, the release of the ADP step is skipped [ 4 ]. Functional tests have indicated that the substrate-binding surface lies on the two α-helices (H and I) of the apical domain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of various switching reactions in the AmAc/ADP data confers an overall lack of cooperative binding of ADP; this conclusion is strengthened by the nMS data showing gaussian distribution for ADP binding at all observed ADP concentrations and by studies conducted by other researchers observing lower affinities associated with the binding of ADP. 28, 51 It has been shown that binding of ADP can cause conformational shifts in GroEL, 52 which are corroborated possibly by the entropic domination seen for GroEL-ADP5-9. However, these entropic shifts do not seem to be resultant from an allosteric transition 37 that leads to increased affinity for further ligation reactions.…”
Section: Resultsmentioning
confidence: 90%
“…Lastly, this study represents the first directed separation of high-resolution GroEL-substrate complexes (or GroEL complexes of any kind) by single-particle cryo-EM. When applied to previous and future GroEL data sets, this focus-cleaning strategy should further remove significant heterogeneity and improve resolvability and map quality, revealing hitherto unseen, biologically relevant GroEL features and/or structures [2, 4, 6, 38, 39].…”
Section: Discussionmentioning
confidence: 99%